Psychological risk indicator in oncology: development and evidence of validity - Souza,Juciléia (2023)
Abstract The authors developed and validated a novel psychological screening instrument including a set of predictors of adaptation present in the literature. By combining meaningful predictors, the new scale's purpose is to screen vulnerable cancer patients before the development of higher levels of distress. This novel scale was named Psychological Risk Indicator in Oncology (i.e., in Brazilian Portuguese Indicador de Risco Psicológico em Oncologia - IRPO). The objective of this article is to describe the IRPO development and the finding of evidence of the validity. The method had two different phases: 1 - instrument development and factorial analysis; 2 - predictive validity analysis and normatizing of scale. In Phase 1, the Psychological Risk Indicator in Oncology (IRPO) was developed and administered to 300 cancer patients with five factors (27 items) identified in the exploratory factorial analysis: distress; active coping; emotional social support; instrumental social support; and negative perception of illness. The overall test score achieved a good level of reliability (α=0.90). In Phase 2, 98 cancer patients were evaluated with the IRPO and the Hospital Anxiety and Depression Scale (HAD), which was used as the criterion variable to verify predictive validity. The factorial structure of the IRPO maintained good stability and demonstrated good predictive power in relation to the HAD (R 2 = 0.59). Factorial, internal consistency, correlations, and regression analyses indicated that the IRPO demonstrated evidence of validity and reliability, and also confirmed the viability of the recommended psychometric parameters to evaluate cancer patients at psychological risk.